The dynamics of environmental movements: the case of the environmental movement in the Municipality of Icapuí/CE (Research, Society and Development, 2020)
The social movements around Nature Conservation Units (NCU) have a major role concerning awareness and change of attitude towards the environment. In place such as Icapuí municipality, located in Ceará state, Northeastern Brazil, local environmental movement development culminated in an Environmental Protection Area (EPA). Having said that, after EPA was established it was seen a decline in their actions. As such, the aim of this study is to evaluate the Environmental Movements (EM) actions in Icapuí before and after the creation of APA Barra Grande (EPAMBG). In order to do that the current research addresses the following question: Was there a continuity in the actions related to mangrove ecosystem preservation in Icapuí Municipality after EPA Barra Grande (APAMBG)? This study uses a qualitative framework, starting with bibliographic research. It is the case study. In the data collection made use of Oral History. In addition, a non-probabilistic technique Snow Ball and semi-structured interviews were used. The social actors were categorized in five groups: Ecological, Municipal Management, Students, Teachers and NGOs. The analysis suggests that over the past few years there was a decline of the EM in Icapuí, however not exclusively by the APA creation; among others aspects, there was the lack of public investment in the environmental area.